Verbal Emotional Disclosure of Moral Injury in Holodomor Survivors - Лариса Засєкіна; Сергій Засєкін (Психолінгвістика)
Objectives. The purpose of the current research is to define and operationalize moral injury based on moral standards, moral judgements, moral reasoning, moral emotions, moral behaviour, and moral consequences; to explore verbal emotional disclosure of moral injury in Holodomor survivors’ narratives.